2007
DOI: 10.1124/dmd.106.013797
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Distribution, Metabolism, and Elimination of the Direct Renin Inhibitor Aliskiren in Healthy Volunteers

Abstract: Aliskiren (2(S),4(S),5(S),7(S)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 29 publications
(27 reference statements)
1
99
0
2
Order By: Relevance
“…Aliskiren has a molecular weight (551.8) small enough to be filtered by the glomerulus, and indeed the drug appears in the urine. 83 Thus, in vivo exposure of podocytes to aliskiren is predicted. As podocytes express a functional RAAS, [25][26][27][28] renin inhibition in these cells by aliskiren may Effect of aliskiren and enalapril on blood pressure (a) and albumin excretion (b) in mRen-2 rats.…”
Section: Testing Aliskiren In Animal Modelsmentioning
confidence: 99%
“…Aliskiren has a molecular weight (551.8) small enough to be filtered by the glomerulus, and indeed the drug appears in the urine. 83 Thus, in vivo exposure of podocytes to aliskiren is predicted. As podocytes express a functional RAAS, [25][26][27][28] renin inhibition in these cells by aliskiren may Effect of aliskiren and enalapril on blood pressure (a) and albumin excretion (b) in mRen-2 rats.…”
Section: Testing Aliskiren In Animal Modelsmentioning
confidence: 99%
“…5 Aliskiren exhibits a long terminal elimination half-life of approximately 40 h, 6,7 and has shown effective 24-h BP control in ambulatory BP-monitoring substudies. 8 Moreover, clinical studies in patients with hypertension have shown that the effect of aliskiren to lower BP and reduce plasma renin activity (PRA) persists for up to 2 weeks after stopping treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Aliskiren is primarily eliminated by the hepatobiliary route as unmetabolized drug. Less than 1% of an orally administered dose is excreted in the urine as unchanged drug (Waldmeier et al, 2007). After oral administration of a single 300-mg dose of aliskiren to healthy volunteers, the mean ± SD clearance corrected for bioavailability [i.e., clearance/drug bioavailability (Cl/F)] was 234 ± 137 L/hour (Zhao et al, 2006).…”
Section: Pharmacokinetic Properties Of Aliskirenmentioning
confidence: 99%
“…The pharmacokinetic properties of aliskiren have been studied in animals, healthy human subjects, patients with compromised liver and kidney function, and subjects with mild hypertension (Waldmeier et al, 2007). Aliskiren has a poor bioavailability (2-6%), but this is compensated by its high solubility and the already mentioned high inhibitory effect (IC 50 = 0.6 nM) from in vitro inhibition of human renin (Wood et al, 2005;Azizi et al, 2006).…”
Section: Pharmacokinetic Properties Of Aliskirenmentioning
confidence: 99%